E-LEARNING IN HIGH SCHOOL TRAINING: FEATURES AND COMPLEXITY OF IMPLEMENTATION - S. A. Dochkin; E. S. Michurina; G. G. Tupikina (Вестник Кемеровского государственного университета, 2015)
The paper summarizes the research whose purpose was to identify the factors and conditions affecting the dynamics of implementing e-learning in higher education in the region. The results of the analysis on using e-learning in higher education and the basic challenges reducing the rate of using these information systems were presented. The authors identified a number of activities that enhance this process, namely: the need for organization and management of this process, the systematic training of teachers, complex training of students, pedagogically reasonable integration of electronic and traditional teaching.